The Role of Airlines in Sport Sponsorship - Váczi, Péter; Rakaczki, Zoltán; Hédi, Csaba (Acta Carolus Robertus, 2024)
The close relationship between global sporting events and airlines has long been recognized as a strategic alliance that helps increase the brand value of both parties. Sports sponsorship as a marketing tool enables airlines to broaden their target audience, increase their brand awareness and deepen their customer relations. The start of airline sponsorship in sports roughly coincides with when sports really became a business. When it comes to sports sponsorship, airlines are in a unique position as their products and services are directly linked to the global nature of sporting events. In this thesis, we examine the sponsorship perception and methods of the most important participants in this industry in the field of sports. Finally, we try to draw conclusions about how profitable it is for these business actors to carry out sponsorship practices in the field of sports.